Social Capital-Based Youth Empowerment To Prevent The Development of Radicalism in the City of Bandar Lampung: Pemberdayaan Pemuda Berbasis Social Capital Untuk Mencegah Perkembangan Radikalisme Di Kota Bandar Lampung - Astiwi Inayah; Agus Hadiawan; Aman Toto Dwijono (Ragom Jurnal Pengabdian Masyarakat, 2023)
The problem of radicalism in Lampung requires very serious handling because Lampung is included in the red light category for understanding radicalism and terrorism. One way to deal with it is to do prevention from within. The younger generation is a vulnerable target for radicalism and terrorism. The handling of radicalism cannot only rely on the government, but must also receive full support from the community, including the younger generation. The purpose of implementing this Community Service activity is to provide social capitalbased assistance for youth organizations in Bandar Lampung City to prevent the development of radicalism. The activities carried out are in the form of group discussion forums (FGD) and are accompanied by assistance to increase youth understanding regarding the prevention of radicalism by utilizing 3 dimensions of social capital, namely trust, social networks, and social institutions. Participants involved in this activity totaled 16 people 27 consisting of members of various youth organizations in the city of Bandar Lampung. The methods used in this activity include the stage of increasing cognitive aspects and the mentoring stage. In particular, this service activity leads to several objectives, including: on the cognitive aspect, there is an increased understanding of the importance of the role of youth in helping the government to prevent the development of radicalism, while on the practical aspect, this assistance is expected to make youth play an increasingly active role in preventing radicalism.